UPAYA MENINGKATKAN KEMAMPUAN GURU SMP NEGERI NUBA ARAT KECAMATAN KANGAE DALAM MENGELOLA PEMBELAJARAN MELALUI SUPERVISI KLINIS PADA SEMESTER GENAP TAHUN PELAJARAN 2018/2019 - ANGELINUS WONGGA (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
Teachers at the SMPN Nuba Arat District Kangae Sikka District, 76.68% was a newteacher and energy Honorer. Preliminary supervision results show teachers teaching bypromoting lectures. Whereas the demands of the 2013 curriculum, in the process of learningin the classroom using step 5M is observing, Minister, collecting information/trying,menalar/associating. Therefore, in ensuring the implementation of the principal task teachers E-ISSN 2686 5661VOL.01 NO. 12. JULI 2020 INTELEKTIVA : JURNAL EKONOMI, SOSIAL & HUMANIORA28 ANGELINUS WONGGAmust be supervised. Clinical supervision is a form of professional guidance given to theteachers based on their needs through a systematic cycle of planning, careful observation ofthe implementation and assessment of the results of the observation immediately andobjectively about the teaching appearance. The clinical supervision cycle corresponds to acycle in school action Research (PTS), each cycle consists of four phases of activity i.e.planning, implementation, observation, and Reflection (Arikunto, 2011).This PTS is held in the even semester of lesson 2018/2019 for 4 months which is fromthe second week of January to the second week of May 2019, with a target of 19 teachers ofsubjects. PTS are conducted in two cycles, and are declared successful when the averageachievement of each indicator > 80%. The results of the pre-vision cycle acquired data 1)teacher's ability to compile RPP is 47.37% (very less) and 2) teachers ' ability in the learningprocess according to the curriculum 2013 is 35.79% (very less). Through mentoring in cycleI, obtained the average achievement of pedagogic competence teachers in: 1) drafting RPP is62.41% (less) and 2) learning process According to curriculum 2013 is 51.05% (good). Thusthe study was declared successful, and it can be concluded that through clinical supervisioncan improve the competency of SMPN teachers Nuba Arat in conducting learning based oncurriculum 2013 at the even semester of lesson 2018/2019.